Analysis of the Application of Accounting Information Systems for Cash Sales and Cash Receipts in the Company: Analisis Penerapan Sistem Informasi Akuntansi Penjualan Tunai dan Penerimaan Kas pada Perusahaan - Maskur, Ali; Hermawan, Sigit (Universitas Muhammadiyah Sidoarjo, 2018)
The research belongs to the type of qualitative research, involving 3 informants as the main data source which is the leader and the staff at the CV. Sumber Abadi DeterSystem and cash receipts an the continuity of the performance process in the company CV. Sumber Abadi Determination of informant was chosen according to the relationship with the title of the researcher by making observation first in all the scope of the leadership and company staff CV. Sumber Abadi. The analysis tools used are data collection, data reduction, data display, and conclusion by paying attention to the data validity test equipment which includes credibility test, transferability test, dependability test, and confirmability test. The results of this study indicate the development of concept and theories that already exist in the accounting aspects of loading; 1) the existence of functions related to accounting information system for cash sales and cash receipt at CV. Sumber Abadi, cash receipt staff, the function of gunang employes, the accounting, function. 2) there are documents that are used such as order and sales note. 3) reports used are sales recap, card stock, credit card, proof of deposit and HPP recap. 4) the notes used are sales record and petty cash book records. And with the control starting from the elements of the organization authorization system, elements of healthy, practices up to the process of the system running